Vulnerabilities in Yersinia pestis caf Operon Are Unveiled by a Salmonella Vector - Cao, Ling; Lim, Timothy; Jun, SangMu; Thornburg, Theresa; Avci, Recep; Yang, Xinghong (PLOS ONE, 2012)
During infection, Yersinia pestis uses its F1 capsule to enhance survival and cause virulence to mammalian host. Since F1 is produced in large quantities and secreted into the host tissues, it also serves as a major immune target. To hold this detrimental effect under proper control, Y. pestis expresses the caf operon (encoding the F1 capsule) in a temperature-dependent manner. However, additional properties of the caf operon limit its expression. By overexpressing the caf operon in wild-type Salmonella enterica serovar Typhimurium under a potent promoter, virulence of Salmonella was greatly attenuated both in vitro and in vivo. In contrast, expression of the caf operon under the regulation of its native promoter exhibited negligible impairment of Salmonellae virulence. In-depth investigation revealed all individual genes in the caf operon attenuated Salmonella when overexpressed. The deleterious effects of caf operon and the caf individual genes were further confirmed when they were overexpressed in Y. pestis KIM6+. This study suggests that by using a weak inducible promoter, the detrimental effects of the caf operon are minimally manifested in Y. pestis. Thus, through tight regulation of the caf operon, Y. pestis precisely balances its capsular anti-phagocytic properties with the detrimental effects of caf during interaction with mammalian host.